Viscometric and Activation energy study of PEG 6000 in water , and solution of DMSO with water at 298.15k , 308.15 , 318. (Journal of the College of Basic Education, 2019)
on the basis of viscosities of PEG 6000 in water and in mixed aqueous solution of DMSO at 298.15 ,308.15 , 318.15 k , kinematic viscosity and the Activation Energy have been calculated using Erying equation .The result are discussed in the light of Erying theory and shows that the DMSO solution preferred than water